A 20-MHz 0.323-mW 23.9-dBm-IIP3 4th-order current-reuse lowpass filter - Thanapitak, Surachoke; Chulajata, Tatcha; Sedtheetorn, Pongsatorn; Hayatleh, Khaled; Surakampontorn, Wanlop (My University, 2021)
A source follower lowpass filter which has a capability of bulk-attenuation cancellation in higher order is presented. Under strong inversion bias arrangement for high frequency application, this fourth-order-filter is simulated in a 0.18 μm standard CMOS process and exhibits a 20 MHz bandwidth with total power consumption of 0.323 mW from 1.8 V supply. Third order intermodulation distortion verification with 1.9 and 2.1 MHz signal archives 23.9 dBm IIP3 with 75.5 dB dynamic range. By using figure-of-merit as a benchmark indicator, the proposed filter is one of the top in its class with the lowest power consumption.
Keywords: Low Power; Source Follower Filter